2019
DOI: 10.1111/dom.13866
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic control in patients with type 2 diabetes initiating second‐line therapy: Results from the global DISCOVER study programme

Abstract: Aim To assess glycaemic control and factors associated with poor glycaemic control at initiation of second‐line therapy in the DISCOVER programme. Materials and methods DISCOVER (NCT02322762 and NCT02226822) comprises two similar prospective observational studies of 15 992 people with type 2 diabetes (T2D) initiating second‐line glucose‐lowering therapy in 38 countries across six regions (Africa, Americas, South‐East Asia, Eastern Mediterranean, Europe and Western Pacific). Data were collected using a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 32 publications
0
26
1
Order By: Relevance
“…These findings suggest that HbA1c levels are not measured routinely in all countries, although other reasons such as a lack of recording of HbA1c data by physicians may also be responsible. 11 Patients in DISCOVER also had a high burden of vascular complications at baseline: the age-and sex-standardized prevalence of microvascular and macrovascular complications was 17.9% (ARR 14.2%-20.4%) and 9.2% (ARR 4.1%-18.8%), respectively, which is concerning given that these patients are at a relatively early disease stage (median time since diagnosis of T2D at baseline was 4.1 years). 12 Other important investigations, including measurements of estimated glomerular filtration rate, urine albumin-to-creatinine ratio and lipid variables, were carried out even less frequently than HbA1c level measurement, and the use of preventive treatments, such as statins, was lower than expected in this patient population.…”
Section: Key Findings To Datementioning
confidence: 98%
See 1 more Smart Citation
“…These findings suggest that HbA1c levels are not measured routinely in all countries, although other reasons such as a lack of recording of HbA1c data by physicians may also be responsible. 11 Patients in DISCOVER also had a high burden of vascular complications at baseline: the age-and sex-standardized prevalence of microvascular and macrovascular complications was 17.9% (ARR 14.2%-20.4%) and 9.2% (ARR 4.1%-18.8%), respectively, which is concerning given that these patients are at a relatively early disease stage (median time since diagnosis of T2D at baseline was 4.1 years). 12 Other important investigations, including measurements of estimated glomerular filtration rate, urine albumin-to-creatinine ratio and lipid variables, were carried out even less frequently than HbA1c level measurement, and the use of preventive treatments, such as statins, was lower than expected in this patient population.…”
Section: Key Findings To Datementioning
confidence: 98%
“…In nine countries, eight of which had middle‐income economies, HbA1c levels were missing for >30% of participants. These findings suggest that HbA1c levels are not measured routinely in all countries, although other reasons such as a lack of recording of HbA1c data by physicians may also be responsible . Patients in DISCOVER also had a high burden of vascular complications at baseline: the age‐ and sex‐standardized prevalence of microvascular and macrovascular complications was 17.9% (ARR 14.2%‐20.4%) and 9.2% (ARR 4.1%‐18.8%), respectively, which is concerning given that these patients are at a relatively early disease stage (median time since diagnosis of T2D at baseline was 4.1 years) .…”
Section: The Global Discover Studymentioning
confidence: 99%
“…However, global outcomes data are sparse for new therapies in people with type 2 diabetes, especially outside North America and Europe. Previous studies have shown large variations in the management of people with diabetes and the prevalence of complications [ 5 , 6 ]. More recently, global collaborative studies have shown that there are differences in patient characteristics, treatment patterns, and types of adverse CVD events experienced by patients in different regions and different ethnicities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the efforts to improve the treatment of T2D with the development of new drugs, the percentage of patients achieving optimal glycemic control (HbA1c < 7.0%) is still lower than desired, and mortality remains high, indicating the necessity of new therapies for T2D [ 14 ]. The global perspective DISCOVER study program demonstrated that exists a failure to monitor blood glucose in T2D patients that results in poor levels of glycemic control at initiation of second line therapy, particularly in lower-middle- and upper-middle-income countries [ 15 ]. At this stage of treatment, 26.7% of the tested patients had an HbA1c level ≥ 9.0% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global perspective DISCOVER study program demonstrated that exists a failure to monitor blood glucose in T2D patients that results in poor levels of glycemic control at initiation of second line therapy, particularly in lower-middle- and upper-middle-income countries [ 15 ]. At this stage of treatment, 26.7% of the tested patients had an HbA1c level ≥ 9.0% [ 15 ]. Lack of efficiency was the most stated reason for choosing a second-line therapy, followed by physician preference, patient request, and side effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%